A new Trogoderma from Madagascar (Coleoptera: Dermestidae: Megatominae), with a key to Madagascan species of the genus - Háva, Jiří; Trýzna, Miloš (Zootaxa, 2022)
Trogoderma banari Háva & Trýzna sp. nov., from central Madagascar is here described. Male genitalia are illustrated, and colour photographs of the species are provided. The new species differs from similar species by the combination of the following characters: colour of the elytral fasciae, the structure of the antennae, and the shape of the male genitalia. A key to the known Madagascan species of the genus Trogoderma is provided.